Sanliurfa and Harran Plains On-Farm and Village Development Project - Kudat, Ayse (World Bank, Washington, DC, 2012)
This social assessment (SA) is part of the Sanliurfa and Harran On-farm Development Project in Turkey, and aims at identifying an appropriate mix of project inputs to reduce poverty. The objectives of the SA are to understand the impact of rapid agricultural modernization on various social groups, according to ownership criteria, and gender issues, and, to learn how those benefiting from irrigation, assess the quality of technical services they are receiving, as well as what expectations they hold for the future. The note finds that a rapid shift in cropping patterns resulted from the agricultural transition, as well as increases in farm equipment and tractor ownership. However, sharecropping compares unfavorably to the usual percentage arrangements made for rain-fed agriculture, while current asset distribution, i.e., land, livestock, farm equipment, and income is highly unequal, and, tribal affiliation, though serves as social safety nets, fosters illiteracy, and land tenure inequities, particularly among women. Recommendations include effective extension services, and livestock intensive practices, which would create employment opportunities for landless laborers, and increase income-earning potential, and, participatory structures such as infrastructure, and institutional development should be considered, for it constitutes the interface between technology and best agricultural practices.